Peningkatan Motivasi Belajar dan Hasil Belajar Kimia Peserta Didik Kelas XI MIPA dengan Model Pembelajaran Kooperatif STAD - Bekti Mulatsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
This study aims to increase learning motivation and chemistry learning outcomes of students of class XI IPA 1 of SMAN 1 Banguntapan 2018/2019 academic year on Salt Hydrolysis material through the application of the STAD type cooperative learning model (Student Teams Achievement Divisions). The learning motivation observed consisted of aspects of choice, confidence for success, and tenacity in trying. This type of research is Class Action Research (CAR). This research was conducted in two cycles with the subjects of the XI IPA 1 class students of SMAN 1 Banguntapan 2018/2019 academic year as many as 34 students. Data collection was carried out by observation, filling in learning motivation questionnaires, giving quiz questions, and document studies. The instruments used to collect data in this study were observation sheets for the implementation of learning, Student Worksheets, learning motivation questionnaires, quiz questions, and documents. Analysis of data from observation of learning activities, questionnaires, quiz questions, and documents carried out through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the application of STAD type cooperative learning correctly through five stages of TGT cooperative learning consisting of stages of class presentations, group learning, group presentations, quizzes, and group awards, can increase learning motivation and chemistry learning outcomes. Based on the results of the questionnaire, the percentage of students who had high learning motivation in the first cycle was 64.71%, while in the second cycle there were 82.35%. Based on the implementation of the quiz the learning outcomes of students also increased, in the first cycle the percentage of students reached KKM was 29.41%, while in the second cycle it was 61.75%.